Electrical and photovoltaic properties of a n-Si/chitosan/Ag photodiode - Akkilic, Kernal; Yakuphanoğlu, Fahrettin (Elsevier, 2008)
The electrical and photovoltaic properties of AuSb/n-Si/chitosan/Ag diode have been investigated. The ideality factor, barrier height and Richardson constant values of the diode at room temperature were found to be 1.91, 0.88 eV and 121.4 A/cm(2) K-2, respectively. The ideality factor of the diode is higher than unity, suggesting that the diode shows a non-ideal behaviour due to series resistance and barrier height inhomogeneities. The barrier height and ideality factor values of Ag/CHT/n-Si diode at room temperature are significantly larger than that of the conventional Ag/n-Si Schottky diode. The phi(B) value obtained from C-V measurement is higher than that of phi(B) value obtained from I-V measurement. The discrepancy between phi(B)(C-V) and phi(B)(I-V) barrier height values can be explained by Schottky barrier height inhomogeneities. AuSb/n-Si/chitosan/Ag diode indicates a photovoltaic behaviour with open circuit voltage (V-oc = 0.23 V) and short-circuit current density (I-sc = 0.10 mu A/cm(-2)) values. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: organic semiconductor; photovoltaic behaviour; barrier height inhomogeneity